2021
DOI: 10.18844/ijlt.v13i1.5279
|View full text |Cite
|
Sign up to set email alerts
|

Examination of opinions of elementary school students on Mathematics course in the COVID-19 pandemic process

Abstract: As a virus which affected the world in general, the covid-19 pandemic has also created negative results on education. In this study, it was aimed to examine the opinions of elementary school students in Covid-19 pandemic process on mathematics course. The participants of the study were fifth grade elementary school students enrolled at elementary schools affiliated with the Ministry of National Education and Culture in Northern Cyprus. This study is a descriptive research and survey method was used in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Majority of the students stated that they use the internet every day during the pandemic period, and it was determined by this research that most of them stayed connected to the Internet for 4 hours or more per day. During the Covid-19 Pandemic period, it was found that male students experienced significantly higher problematic internet usage than female students (Tezer et al, 2021). In addition, it was determined that male students showed more academic procrastination behaviors than female students.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the students stated that they use the internet every day during the pandemic period, and it was determined by this research that most of them stayed connected to the Internet for 4 hours or more per day. During the Covid-19 Pandemic period, it was found that male students experienced significantly higher problematic internet usage than female students (Tezer et al, 2021). In addition, it was determined that male students showed more academic procrastination behaviors than female students.…”
Section: Discussionmentioning
confidence: 99%
“…They referred because primary school students are active and joyful to move, those who are used to studying in school activities with their friends, but during this pandemic period, students are compelled to stay at home exclusively, pupils felt saturated. While a substantial number of pupils struggled to understand mathematics class during the pandemic, most of them enjoyed learning mathematics (Tezer et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the pandemic, many had problems understanding coursework. Students complained about lessons, materials, and homework (Tezer et al, 2021). As a result, learners' academic performance declined (Soysal et al, 2022).…”
Section: Academic Performance During Covid-19 Pandemicmentioning
confidence: 99%